Double ARA-Sumudu decomposition method for the solution of linear fractional partial integro-differential equations - Jagdish Nanaware; Akshaykumar Dongardive (Mathematics and Computational Sciences, 2025)
This paper focuses on deriving the exact solution to the linear fractional partial integro-differential equation through the application of the double ARA-Sumudu transform. By leveraging the double ARA-Sumudu transform, a decomposition method is constructed using the definition of the Caputo fractional derivative. Surface graphs of solutions are provided for visualization purposes.